Bridging the Digital Divide in the US: Planning Innovative State and Local Approaches (Community Development Research and Practice Series, 2025)
The US faces a deep digital divide which cuts across both urban and rural lines, but is most marked in rural, low income, and minority communities. This book presents a multi-level governance framework which explores how local leaders use policy opportunity and community resilience to address inequity in broadband infrastructure. Cases from communities across the US are profiled to show how local and regional initiatives address the digital divide – how they harness local resources, state and federal funding, and how they navigate regulatory restrictions and financial constraints. Special attention is given to rural and Indigenous communities, where the technological, organizational, and funding challenges are greatest. The federal policy landscape for broadband is changing, and this book provides clear insights on how policy can support the people and places left behind. This book is essential for planners and those studying or working in rural development, rural studies, and community development. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial (CC-BY-NC) 4.0 license.